AKAD PERJANJIAN SISTEM BAGI HASIL ANTARA NELAYAN DAN PEMILIK KAPAL DI DESA TANJUNG SALEH KUBU RAYA - Dzikron Dzikron; Abu Bakar; Nanda Himmatul Ulya (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
The purpose of this research is to assess the cooperation between fishermen and boat owners in Tanjung Saleh Village by analyzing the rights and obligations in the contract agreement between the two parties. The sources of data in this study are ship owners and fishermen. So, this research was conducted using a descriptive method with a qualitative approach. Techniques and data collection tools were observation, interviews, and documentation that presented data for profit sharing between ship owners and fishermen. Data management and data analysis techniques use an interactive model with the stages of data collection, data reduction, data presentation, and conclusion drawing that are presented in a comprehensive, comprehensive manner. The results of this study indicate that the cooperation between fishermen and boat owners can be said to be mutually beneficial and there is an initial agreement on the profit sharing, which is 50:50. The first 50% is for paying fishermen's wages of 20%, employees or staff get 15%, and the next 15% is for purchasing boat oil to prepare fishermen for the next day. While the next 50% is for the ship owner and if there is damage such as repairing the ship, damaged fishing nets, leaking ships, and purchasing paint, the ship owner will also bear the damage to the ship. The contract made by the owner of the ship and the fisherman was not written but was witnessed by three witnesses.